Thermal and ultrasonic properties of Estremoz Marbles, Portugal - Alves, Tiago (2018)
Thermal and ultrasonic properties are non-destructive methods used to determine dimension stones anisotropy. Both methods are very simply to operate and give results quickly, nevertheless in particular rocks of visible textural anisotropy such as the Estremoz Marbles, a special care must be taken when doing the cubic samples to test. In fact to get better results one of the cube face must be parallel to the foliation plane (XY), so the others are perpendicular and one them must be cut along the stretching direction (XZ), consequently the third face of the cube (YZ) will be perpendicular to the others (also to the local fold axis when it is present). An ultrasonic standardization will enable the determination of possible structural defects, such as discontinuities, which may exist within marketable blocks, noticeable for instance, when speeds are lower than typical for marbles observed. The thermal properties are particularly important when processes related with heating and cooling of buildings must be considered. It’s know that dimensions stones processing efficiency, as well as aesthetical characteristics, could be improve if the stones anisotropy are considered. Combine these two parameters an expedite procedure could guide stone manufacturer to obtain better results from the quarry to the final products.